Increased nitration and diminished activity of copper/zinc superoxide dismutase in placentas from diabetic rats - White, Verónica (2010)
Nitration-induced protein damage in the placenta leads to impaired blood flow and deficient feto–placental exchange in diabetic pregnancies. This work studied the effect of nitric oxide and peroxynitrite on Cu/Zn SOD activity in rat placentas and evaluated whether Cu/Zn SOD is nitrated in the placenta from diabetic rats at mid-gestation. Protein nitration was evaluated by EIA, Cu/Zn SOD activity by inhibition of the epinephrine auto-oxidation, Cu/Zn SOD expression by western blot and specific nitration by immunoprecipitation. This study found higher levels of protein nitration (p < 0.001), diminished Cu/Zn SOD activity and enhanced protein expression (p < 0.01) in placentas from diabetic rats. Placental Cu/Zn SOD activity was inhibited by peroxynitrite (p < 0.01). Besides, nitration of Cu/Zn SOD was elevated in placentas from diabetic rats (p < 0.01). These results show that rat Cu/Zn SOD can be nitrated, a modification that could lead to the depressed activity of this enzyme found in placentas from diabetic rats.